Formation of silicon layer through aluminothermic reduction of quartz substrates - Islam, Muhammad Monirul; Sawahata, Junji; Akimoto, Katsuhiro; Sakurai, Takeaki (Frontiers in Materials, 2022)
Silicon (Si) films were obtained through aluminothermic reduction of the quartz (SiO2) substrates, where the surface of the quartz in contact with the deposited aluminum (Al) layer has been converted to elemental Si during high-temperature annealing. X-ray diffraction (XRD) patterns and Raman spectra show dominating peaks corresponding to elemental Si in the obtained films. Energy dispersive spectroscopy (EDS), as well as XRD of the obtained Si layer, suggests that reduction products consist of mainly elemental Si mixed with oxides of Al-related phases. Both the higher reaction temperature and high initial Al-content (larger thickness of Al film in Al/SiO2 structure), studied in this paper, were found in favor of obtaining higher contents of Si in the obtained films. Thus, crystallinity and quality of the obtained Si-layer improve with the increase of both reduction temperature as well as thickness of the Al layer, as confirmed by XRD and Raman spectra. The aluminothermic reduction mechanism has been discussed using XRD as well as a ternary phase diagram of the constituent elements, obtained from EDS data. Crystalline nature (nanocrystal to microcrystal to polycrystal) and the crystalline quality of the obtained Si layers were found to be affected by the thickness of the deposited Al layer on SiO2 substrates.